2006
DOI: 10.1007/s00170-006-0666-4
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of multi-functional micro parts by two-component metal injection moulding

Abstract: Several metals and alloys can be used to enhance the mechanical and physical properties of micro parts and components for micromechanical, micro-chemical or sensor applications. Such parts can be produced in series by the powder metallurgical process of micro metal injection moulding (my-MIM). This paper describes a novel manufacturing route for metallic multi-material micro components, two-component micro metal injection moulding (2C- my-MIM). Similar to 'two-colour' injection moulding of plastics, the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 2 publications
0
25
0
1
Order By: Relevance
“…It is also the subjects to improve strength and dimensional accuracy (Miura 1999 For miniature fabrication LIGA (Becker et al 1986) or micro-machining have been developed, but they have limitation of applicable materials and production capacity. On the other hand, l-MIM broadens the selection of the materials for micro applications (Imgrund et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…It is also the subjects to improve strength and dimensional accuracy (Miura 1999 For miniature fabrication LIGA (Becker et al 1986) or micro-machining have been developed, but they have limitation of applicable materials and production capacity. On the other hand, l-MIM broadens the selection of the materials for micro applications (Imgrund et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Love and Goodship [18] analysed the performance of multimaterial injection moulding. There are also studies about the performance of multimaterial powder injection moulding, in this case Liu et al [19] did it for an Al-AlN metal matrix composite, Heaney et al [20] for tool steel and boron doped austenitic stainless steel, Imgrund et al [21] for non-magnetic and a ferromagnetic stainless steel and Liu et al [22] for aluminium (Steel and Magnet) Hybrid components. These technologies have been found to have several problems: melting of the metallic inserts, degradation of insert properties, component cracking owing to mismatches in the coefficient of thermal expansion, and severe interfacial reactions between the insert and host material like Liu et al reported [22] .…”
Section: New Design and Manufacture Strategymentioning
confidence: 99%
“…Second, during hightemperature sintering, diffusion of alloying elements along the boundary occurs and unwanted phases might be formed, which can deteriorate the properties. Experiments performed on the fabrication of composite layers from stainless steels, superalloys, tool steels, iron, low carbon steels, hardmetals, and ceramics [14][15][16][17][18][19][20] have revealed that the sintering process is the key step in the manufacturing route. Apart from its technical importance, co.-sintering of cemented carbide/stainless steel composite structures has not been examined or been reported so far in the open literature.…”
Section: Introductionmentioning
confidence: 99%
“…An obvious development over ''assembling and sintering'' is the copowder injection molding process, which has been found as a potential manufacturing route for the fabrication of two-component parts. [11][12][13][14][15] In this method, a two barreled injection molding machine is used. This allows injection of two different feedstocks either simultaneously or in subsequent stages in one molding machine.…”
Section: Introductionmentioning
confidence: 99%